2007
DOI: 10.1007/s00213-007-0934-5
|View full text |Cite
|
Sign up to set email alerts
|

Pro-cognitive effects of 5-HT6 receptor antagonists in the social recognition procedure in rats: implication of the frontal cortex

Abstract: These results indicate that 5-HT6 receptors modulate social recognition by actions in the FCX and underpin their pertinence as targets for the treatment of psychiatric disorders in which cognitive function is compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 68 publications
3
66
0
1
Order By: Relevance
“…abolished both the WAY-181187-induced and the scopolamineinduced social recognition deficit, further reinforcing the notion that 5-HT 6 receptor blockade improves cognitive function by modulating central cholinergic tone. The site of action for these studies was confirmed as being within the frontal cortex (using bilateral direct injections of WAY-181187 and SB-271046), 24 a key area involved with modulating cognitive function in this social recognition paradigm and one in which 5-HT 6 receptor localization has been reported. SB-399885 (1-30 mg/kg, p.o.)…”
Section: Cognitive Enhancing and Behavioral Profiles Of 5-ht 6 Receptmentioning
confidence: 64%
See 1 more Smart Citation
“…abolished both the WAY-181187-induced and the scopolamineinduced social recognition deficit, further reinforcing the notion that 5-HT 6 receptor blockade improves cognitive function by modulating central cholinergic tone. The site of action for these studies was confirmed as being within the frontal cortex (using bilateral direct injections of WAY-181187 and SB-271046), 24 a key area involved with modulating cognitive function in this social recognition paradigm and one in which 5-HT 6 receptor localization has been reported. SB-399885 (1-30 mg/kg, p.o.)…”
Section: Cognitive Enhancing and Behavioral Profiles Of 5-ht 6 Receptmentioning
confidence: 64%
“…24 When suboptimal doses of WAY-181187 and scopolamine were combined in this social memory paradigm, there was a synergistic shift toward a deficit, suggesting that tonic activation of the 5-HT 6 receptor can disrupt cognitive processes linked to reductions in cholinergic tone. Furthermore, SB-271046 (20 mg/kg, i.p.)…”
Section: Cognitive Enhancing and Behavioral Profiles Of 5-ht 6 Receptmentioning
confidence: 93%
“…Furthermore, 5-HT 6 R activates mTOR Complex 1 (mTORC1) in the prefrontal cortex, which is related to cognitive deficits, 2 and the receptor constitutively activates Cdk5 to control cortical neurons migration and promote neurite growth. 3 Blockade of 5-HT 6 R enhances cognitive performance in a broad range of tasks in rodents, 4,5 and phase II clinical studies have demonstrated efficacy of 5-HT 6 R antagonists (Iladopirdine = LuAE58054, SB742457, and AVN-211, Figure 1) in conjunction with donepezil in mild-to-moderate AD patients.…”
Section: T He Most Devastating Neurodegenerative Form Of Dementia Ismentioning
confidence: 99%
“…Acetylcholine has been shown to play a key role in social recognition. Systemic administration of the partial muscarinic cholinergic agonist arecoline or the antagonist scopolamine has been shown to decrease or increase social recognition, respectively (Letty et al, 1997;Millan et al, 2007;Loiseau et al, 2008). Much less is known about the specific involvement of norepinephrine (NE) and, notably, dopamine (DA) and serotonin (5-HT) in social memory.…”
Section: Oxytocin and Social Recognitionmentioning
confidence: 99%
“…Finally, evidence of a role for the serotonergic system has also been observed. The 5-HT 4 and 5-HT 6 receptors have been implicated in social recognition, with the frontal cortex playing a key role in the mediation of these effects (Letty et al, 1997;Loiseau et al, 2008).…”
Section: Oxytocin and Social Recognitionmentioning
confidence: 99%